Violence in the University Environment and the Everyday Lives of UNAM Students: Theoretical and Methodological Explorations in the Face of Mexico’s State Crisis - Pérez, Isaac Enríquez (2025)
Starting from the theoretical difficulties in defining the concept of violence, this article aims to outline a minimal theoretical/methodological strategy that allows structuring —under an interdisciplinary research exercise— studies and opening lines of research aimed at apprehending the meaning and the behavior of violence(s) in the university habitat of a macro-organization such as UNAM. To do this, it is necessary to review the notion of violence in the social sciences, as well as contemporary research that approaches the study of violence in Mexican universities. This with the aim of aiming at the creation of a minimal notion of the concept of violence in the university habitat, which is operative for the investigations that may be derived from this theoretical/methodological proposal. From this notion, it will be possible to construct the categories of analysis to identify the different forms of violence in the university. Beyond the simulation, invisibility and silencing that prevails in the university communities around the violence(s) experienced in these organizations, the thesis that an entity such as UNAM is not alien to social conflict and that This, although it arises in its confines, is exacerbated with the intensification of the state crisis that characterizes Mexico in recent decades.